Greenhouse gases emission trade-offs for benefits gain - An analysis from paddy rice and upland crops cultivation in Hau Giang province, Viet Nam - Tran Thanh Liem Le; Ngoc Nhan Pham; Thi Kim Phuoc Nguyen (CTU Journal of Innovation and Sustainable Development)
Agriculture activities require energy for operation and emit greenhouse gases (GHGs) into the atmosphere. However, agriculture provides essential nutrients with carbon sources through its main and by-products. This study used the life cycle assessment methodology to evaluate the carbon balance in agricultural systems of paddy rice (PR), corn, mung bean (MB), and black sesame (BS) in the summer-autumn growing season in the Vietnamese Mekong Delta. The results showed that PR and upland crops produced a net carbon source of 1,280.9–18,915 kg-C ha–1. Corn cultivation achieved the best value in carbon index analyses. To have one calorie from grain, selected crops must trade off 115.19–501.81 mg-CO2e. This study concluded that four selected crop cultivations achieved carbon analysis benefits. However, corn is a suitable recommendation for adapting to the agricultural conversion from PR farming to better upland crop cultivation.